A solar and thermal multi-sensing microfiber supercapacitor with intelligent self-conditioned capacitance and body temperature monitoring. Issue 23 (4th June 2020) - Teng, Youchao; Wei, Jing; Du, Hongbiao; Mojtaba, Mansoorianfar; Li, Dagang
Abstract : A solar and thermal multi-sensing microfiber supercapacitor was fabricated for photothermal conversion capacitance enhancement and body temperature monitoring. Abstract : A solar and thermal multi-sensing all-solid-state microfiber supercapacitor (ASSMFSC) with prominent electrochemical and mechanical performance, reliable environmental responsivity, and intelligent self-conditioned capacitance was constructed using a cellulose nanofibril-graphene-conjugated polymer, which was assembled as both a core-sheath microfiber electrode (CSMFE) and a sensing unit. The multicomponent hierarchical synergistic design fully exploited the unique attributes and synergistic interaction of each component to endow the well-designed CSMFE with high capacitance and mechanical robustness as well as excellent thermal sensitivity and photothermal conversion, enabling the valid modulation of redox reactions, interface performance, or electronic/ionic transfer in the microfiber supercapacitors toward complex external stimulations and building interrelated working responses. The fabricated ASSMFSC presented a total volumetric capacitance of 85.8 mF cm −3 ( vs. the whole device), excellent cycle stability, and a volumetric energy density of 11.9 mW h cm −3 . Moreover, ASSMFSC showed excellent solar-thermal conversion capacitance enhancement. At one solar power density (1 kW m −2 ), the capacitance was two times that of the device in the dark and the device exhibited self-regulation capacitance ability with the change in the solar intensity. As a thermosensitive device, ASSMFSC with a current sensitivity of 0.47437 ± 0.00549 °C displayed a fast response and excellent reproducibility to sense subtle temperature changes. This work demonstrates that the CSMFE-driven microfiber supercapacitor can be used as a photothermal conversion energy storage system and for body temperature monitoring, which provides an essential reference and optimistic incentives for new generation energy-related devices.